Interactive Courseware: Quranic Verses On The Integration Of Naqli And Aqli Knowledge - Mohammed Akhiruddin Ibrahim; Adnan Mohamed Yusuf; Mohd Zohdi Mohd Amin; Nurlida Basir; Nurazzuwin Adenan; Nurul Atika Azman (International Scientific Academy of Engineering & Technology (ISAET), 2024)
Non-Indexed Publication